Subconjunctival and topical application of recombinant tissue plasminogen activator in rabbits - De Abreu Reggi, José Ricardo; Hida, Richard Yudi; Hida, Milton Massato [UNESP]; Nishiwaki-Dantas, Maria Cristina; Suzuki, Hisashi (GN1 Sistemas e Publicacoes, 2015)
Purpose: To quantify fibrin degradation products after topical and subconjunctival administration of recombinant tissue plasminogen activator in rabbits. Methods: Fibrin formation was induced in the anterior chamber in 25 rabbits. Subsequently, five rabbits received an injection of r-TPA (positive control) in the anterior chamber, another 10 received a subconjunctival injection of r-TPA, and the remaining 10 received instillations of topical r-TPA. Afterwards, samples of aqueous humor were collected and semi-quantitative analysis of fibrin degradation products (FDP) was performed. Results: No statistical differences were noted between the treatment and control groups at any time point. Fibrin degradation products semi-quantification showed statistical improvement in the control group and the subconjunctival group. Conclusion: Fibrin degradation products were observed in the anterior chamber after subconjunctival administration of r-TPA. However, it was probably not sufficient to cause fibrin degradation. Topical r-TPA did not effectively absorb anterior chamber fibrin.
Keywords: Animals; Anterior chamber; Hyphema; Inflammation; Postoperative complications; Rabbits; Tissue plasminogen activator